The Effectiveness Of Video Scribe In Teaching English At SMPN 1 Molawe Konawe Utara - Sessu, Andi; Sahlan, Sahlan; Laepe, Ader (Journal of Language Education and Educational Technology (JLEET), 2018)
The purpose of study is to examine whether or not there was any significant score difference on students’ English achievement before and after treatment by using video scribe. Also, it examined whether or not there was any significant score difference between students are by using taught video scribe and students are taught by using conventional method on their English achievement at the eighth grade of SMPN 1 Molawe. The population of this research was the entire the eighth grade students of SMPN 1 Molawe who enrolled in academic year 2017. This research involved 23 students in experiment class and 25 students in control class. The data were obtained from students’ pre-test and post-test scores. The pre-test was given before the treatment applied and the post test was given after the treatment finished. The finding revealed that there was any significant score difference on students’ English achievement before and after treatment by using video scribe, p (.000) < 0.05. Besides, the finding also indicated that there was a significant difference in the scores for students were taught by using video scribe and students were taught by using conventional method p (.000) < 0.05. In light of all these, video scribe significantly had an effect to students’ English achievement. Moreover, this study merely focused on the effectiveness of teaching English through video scribe, thus it is necessary for the next scholars to examine students’ motivation toward this audio visual aid.